Nursing practice in a remote area : an ethnographic study. - Cramer, Jennifer H. (Curtin University, 1998)
The solitary position of nurses who practise in geographically isolated communities to provide direct health care to a predominantly Aboriginal population characterises nursing in remote areas. Munoz & Mann (1982) described this practice as unique. The uniqueness of this practice, however, has remained shrouded in superficial descriptions featuring service delivery at a one or two-nurse-post, the physical distance of nursing posts from hospital facilities and the autonomy with which nursing is performed. Only glimpses of the reality of nursing practice in a remote area have been revealed through the study of the educational needs of remote area nurses (Munoz & Mann 1982, Cameron-Traub 1987, Philp 1988, Kreger 1991a, Bell, Chang & Daly 1995). A key problem is the lack of a systematic description and detailed analysis of nursing as it is practised in a remote area.The purpose of this study was to explore, describe and analyse nursing practice in a remote area. The research was undertaken at Warburton, an isolated community mainly inhabited by the Ngaanyatjarra people in the Central Desert of Western Australia. An ethnographic design was chosen for this exploratory inquiry into the social and cultural pattern of everyday nursing practice. In a pre-entry study a suitable setting and informants were found. Fieldwork was conducted at the Warburton nursing post by the researcher and involved living on site for a year. Data gathering techniques were participant observation together with interviewing, collection of pertinent documents and the daily chronological recording of fieldnotes, memos and a personal journal. Data analysis was performed concurrently with data gathering. The process followed the Developmental Research Sequence Method by Spradley (1980). Through a cyclical process of data collection and analysis the domains, taxonomies and componential variables in the culture of remote area nursing practice emerged.Amorphous practice was the overall theme revealed in the underlying cultural patterns that shaped the practice of nursing in the remote area. The term amorphous practice is defined as the changeable nature of practice from nurse to nurse, from situation to situation, from time to time. This was observed in the recurrent differences between nurses in their knowledge, abilities and attitudes as well as in the variability between nurses in their management of client care. Contributors to the phenomenon of amorphous practice were found in three distinct, but inter-related, tributary themes termed detachment, diffusion and beyond the nursing domain. Detachment explained the nurses' feelings of separateness from the usual professional and organisational structures needed for the enactment of nursing. Diffusion encapsulated the broad spread of the nurses' role in remote area practice. Beyond the nursing domain described an unregulated practice considered to be outside the responsibilities of nursing care. The substantive theory of amorphous practice provided a detailed description of how nursing was practised in the remote area. It also explained why it was so different from nursing as it is generally understood by the profession.